Methodological directions for research curricula and methods of teaching Sharia sciences in postgraduate studies in universities in the Kingdom of Saudi Arabia from 1429 AH until 1439 AH - ALawaji, Amnah Abdullah; Altwaijri, Ahmed Mohammed (Journal of Educational and Psychological Sciences, 2022)
The study aimed to identify the trends of research curricula and methods of teaching Sharia sciences in graduate studies in the universities of the Kingdom of Saudi Arabia from 1429 AH to 1439 AH, which are related to the researcher’s data and the research method. The descriptive approach based on the content analysis method was applied using the analysis card tool prepared by the researcher and applied to All postgraduate research papers that were approved to obtain master’s and doctorate degrees and related to the curricula and methods of teaching Sharia sciences in the universities of the Kingdom of Saudi Arabia from 1429 AH until 1439 AH, and content analysis was applied to (545) research, including (466) master’s research and (79) research Ph.D., using descriptive statistical methods represented by Cooper’s equation to calculate the stability of the analysis card tool and extract the percentage of agreement, frequencies and percentages to extract the results. The study concluded that the most productive universities for specialization research is Imam Muhammad bin Saud Islamic University, and as for the years, the year 1439 AH was the highest year in which specialization research was approved, and male researchers outperformed females, and also in supervising the research, the male supervisors were The most, and all the research of the study used the quantitative approach except for two researches that used the mixed approach. In the curriculum, the experimental method with a quasi-experimental design was the most used, and most of the research targeted general education, and the most used stages were the intermediate stage, and in the research community, the educated were the highest used. And males are the most targeted in the community, and most of the research used the entire sample, and as for the research tools, most of the research used one tool, and the test tool was used more than others, and most of the tools were prepared by researchers, and as for the statistical methods, the Holstey equation was the most used in calculating stability, and it was used Most researches are descriptive methods, and the most widely used measures of central tendency.